A role for human leucocyte antigens in the susceptibility to SARS‐Cov‐2 infection observed in transplant patients. (5th July 2020) - Poulton, Kay; Wright, Paul; Hughes, Pamela; Savic, Sinisa; Welberry Smith, Matthew; Guiver, Malcolm; Morton, Muir; van Dellen, David; Tholouli, Eleni; Wynn, Robert; Clark, Brendan
Abstract: We analysed data from 80 patients who tested positive for SARS‐CoV‐2 RNA who had previously been HLA typed to support transplantation. Data were combined from two adjacent centres in Manchester and Leeds to achieve a sufficient number for early analysis. HLA frequencies observed were compared against two control populations: first, against published frequencies in a UK deceased donor population ( n = 10, 000) representing the target population of the virus, and second, using a cohort of individuals from the combined transplant waiting lists of both centres ( n = 308), representing a comparator group of unaffected individuals of the same demographic. We report a significant HLA association with HLA‐ DQB1*06 (53% vs. 36%; p < .012; OR 1.96; 95% CI 1.94–3.22) and infection. A bias towards an increased representation of HLA‐A*26, HLA‐DRB1*15, HLA‐DRB1*10 and DRB1*11 was also noted but these were either only significant using the UK donor controls, or did not remain significant after correction for multiple tests. Likewise, HLA‐A*02, HLA‐B*44 and HLA‐C*05 may exert a protective effect, but these associations did not remain significant after correction for multiple tests. This is relevant information for the clinical management of patients in the setting of the current SARS‐CoV‐2 pandemic and potentially in risk‐assessing staff interactions with infected patients.